MODULAR APPROACH TO THE STUDY OF DISPLAYS FOR ELECTRIC VEHICLES - I. I. Shpak; V. I. Kurmashev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The purpose of the work, the results of which are presented in this article was to study the possibilities and different options implementation of the modular approach to developing the content and organization of training. The relevance of such studies is due to the need to train highly qualified specialists in the operation, maintenance and repair of electric vehicles. This professional field is relatively new and actively developing in our country. Therefore, the system of training, retraining and advanced training of personnel for the electric vehicle industry and maintenance of electric vehicles should be flexible and dynamic. Vocational training should be organized in accordance with the changing requirements of the modern labour market. The paper shows the advantages of using modular educational technologies for the organization of professional education in this area. Taking into account the experience gained in the process of training students of the specialty "Industrial electronics" in IIT BSUIR, it is noted that the advantages of the modular approach are increasing many times in combination with the use of modern possibilities of infocommunication technologies and 3D-modeling for training, retraining and advanced training of specialists in electric vehicles. Based on the consideration of the concept of "Modules of labor competencies", developed by experts of the International labor organization, the structure of the modular curriculum for the study of displays, and the modern electric vehicle as a whole is proposed.